METODE LANGSUNG DALAM PEMBELAJARAN BAHASA ARAB - Loeis, Wisnawati (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2011)
Arabic language is known as one of most used language in the world. It is also a way to understand Islamic sources. Direct method is one natural model to learn Arabic which is used by many Islamic schools, both traditional and modern. The method starts by introducing basic words in noun, verb, number, and so on. It also teaches how to write in Arabic well and directly does basic conversation in Arabic